2022
DOI: 10.1093/cid/ciab1053
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infection Transmission Dynamics During the Coronavirus Disease 2019 (COVID-19) Pandemic Among Urban Gay, Bisexual, and Other Men Who Have Sex With Men

Abstract: Background The impact of coronavirus disease 2019 (COVID-19) mitigation measures on sexually transmitted infection (STI) transmission and racial disparities remains unknown. Our objectives were to compare sex and drug risk behaviors, access to sexual health services, and STI positivity overall and by race during the COVID-19 pandemic compared with pre-pandemic among urban sexual minority men (MSM). Methods Sexually active MSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Consistent with research from the USA, respondents from ethnic minority groups were more likely to engage in casual sex than white participants, highlighting the need for culturally relevant health promotion to reach these groups with practical risk reduction advice (Schumacher et al, 2022). Systematic review evidence suggests that MSM from minority ethnic and migrant backgrounds have increased needs surrounding HIV prevention and sexual health.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with research from the USA, respondents from ethnic minority groups were more likely to engage in casual sex than white participants, highlighting the need for culturally relevant health promotion to reach these groups with practical risk reduction advice (Schumacher et al, 2022). Systematic review evidence suggests that MSM from minority ethnic and migrant backgrounds have increased needs surrounding HIV prevention and sexual health.…”
Section: Discussionmentioning
confidence: 58%
“…Increased syndromic management during the pandemic may explain observed proportional declines in male urethral diagnoses and empiric/same day treatment. Fourth, observed declines in reported cases early in the pandemic may, in part, be due to population-level sexual behavior change 18 . This also may explain findings of no change in the frequency of reported symptomatic diagnoses during the pandemic.…”
Section: Discussionmentioning
confidence: 97%
“…Fourth, observed declines in reported cases early in the pandemic may, in part, be due to population-level sexual behavior change. 18 This also may explain findings of no change in the frequency of reported symptomatic diagnoses during the pandemic. Alternatively, observed crude declines in same-day/empiric treatment may be explained by decreased gonorrhea diagnoses at sexual health clinics, as we observed no change in same-day/empiric treatment during pandemic compared with prepandemic when adjusting for diagnosing provider.…”
Section: Discussionmentioning
confidence: 99%
“…A study in China showed that the incidence of HIV infection, syphilis and gonorrhea dramatically declined by 13.1%, 13.8%, and 11.4% in 2020 compared with that in 2019, respectively [ 31 ], although further data related to MSM were not available. Schumacher et al [ 32 ] conducted a study among 231 MSM in US comparing the periods of during vs. prepandemic and found that reports of more than three sex partners and substance use decreased, human immunodeficiency virus/PrEP care engagement increased, STI testing decreased and then rebounded, neither Chlamydia nor gonorrhea positivity significantly changed. In addition, the findings in Amsterdam showed that incidence rates of chlamydia, gonorrhea and syphilis were significantly lower during 15 March 2020 to 15 June 2020, but nonsignificantly higher during 16 June 2020 to 15 September 2020 and during 16 September 2020 to 1 April 2021 of restrictions than in 2019 [ 33 ].…”
Section: Text Of Reviewmentioning
confidence: 99%